Perilaku Pencarian Informasi Generasi milenial untuk Memenuhi Kebutuhan Informasi Mahasiswa Universitas Negeri Padang - Rahmah, Yuni; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractIn this paper the language about Millennial Generation Information Search Behavior To Meet Information Needs. This study aims to describe the information seeking behavior of the millennial generation to meet the information needs of this study at the Padang State University. Data were collected through observation and distribution of questionnaires with students of the Indonesian and Regional Languages and Literature Department at Padang State University. Analyzing the data, concluded the following matters. (1). Starting - consists of activities that initiate information seeking activities. In general (100%) determine the topic especially before conducting an information search, in general (90%) conduct information search after discussion or consultation with lecturers, in general (95.23%) know the information needs when attending lectures, (88.4 %) know the information needs specifically, and in general (88%) do information when they are aware of and know the need for information. (2). Chaining - activities following a series of citations, citations or forms of reconciliation between documents with each other. In general (92.8 uses a bibliography to search information, generally (90.4%) use the author's name from the core reference to look for other references in conducting information searches, and in general (92.9%) use subjects from core reference to look for other references (3) Browsing - merawak, looking for, but rather directed, in areas that are considered to have the potential for the information needed.In general (73%) libraries can always meet information needs, in general In general (95.2%) look for information on the internet if the information you are looking for is not found in the printed source of information, (92.8%) generally directly looking for information on the internet if the information you need is not found in the printed source of information, at generally (45.22%) query identification (keywords). (4). Differentiating - sorting, using the features in the information source as a basic reference for checking quality or information content. in general (88%) the internet is the main source of information, in general (92.84%) The source of information printed is still very much needed in fulfilling information needs. (5). Monitoring - monitoring progress by focusing on selected sources. In general (88.09%) looked for the latest information through the internet by searching for the latest articles, in general (78.56%) needed to find the latest information to enrich the reference sources. (6). Extracting - systematically digging in one source to retrieve information that is considered important. In general (90.47 when you need information you often search the search engine (google, yahoo), in general (88.09 often uses a journal database to get information, in general (78.56%) after getting information on the internet , you directly copy the information, in general (76.19%) use the "Google" search engine because it is more relevant than other search engines.Keywords:Â behavior, millennial generation and information.